2017
DOI: 10.21577/0103-5053.20170040
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Photocatalytic Activity of Pure and N-, B-, or Ag- Doped TiO2

Abstract: This article reports the synthesis and characterization of pure and N-, B-, and Ag-doped TiO 2 and the ability of these oxides to photodegrade methylene blue (MB) under sunlight or UV-ABC radiation. The compounds were synthesized using the sol-gel method and characterized by scanning electron microscopy, X-ray diffraction, diffuse reflectance spectroscopy, Fourier transform infrared spectroscopy, thermogravimetric analysis, and X-ray photoelectron spectroscopy. Photocatalytic efficiency was significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 51 publications
3
11
0
Order By: Relevance
“…As presented in Equation (1), irradiation of the semiconductor with energy higher than its bandgap generates h + in its valence band and e − in the conduction band. If their recombination is avoided, h + can oxidize organic pollutants (P) to their radical cation (Equation (2)) or react with adsorbed water or hydroxyl groups (OH − ) to generate OH ● (Equations (3) and (4)), which in turn oxidize the adsorbed pollutants (Equation (5)) [ 9 , 22 , 34 ]. Photogenerated e − reduce molecular oxygen to form O 2 ●− (Equation (6)), which participates in the acid–base equilibrium with its protonated form (Equation (7)) [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…As presented in Equation (1), irradiation of the semiconductor with energy higher than its bandgap generates h + in its valence band and e − in the conduction band. If their recombination is avoided, h + can oxidize organic pollutants (P) to their radical cation (Equation (2)) or react with adsorbed water or hydroxyl groups (OH − ) to generate OH ● (Equations (3) and (4)), which in turn oxidize the adsorbed pollutants (Equation (5)) [ 9 , 22 , 34 ]. Photogenerated e − reduce molecular oxygen to form O 2 ●− (Equation (6)), which participates in the acid–base equilibrium with its protonated form (Equation (7)) [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The effect of different dopants (B, N, Ag) was studied by Bezerra et al. [31] and they found that the morphology and grain size changed with different type and concentration of dopants.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The photocatalytic activity of TiO 2 can be improved by doping or modifying its crystalline structure in order to increase the optical absorption of radiation in the visible range and decrease the rate of recombination of photogenerated charges [ 22 ]. Light absorption of TiO 2 in the visible region can be improved via metal- [ 23 , 24 , 25 ] or non-metal-doping [ 18 , 26 , 27 ]. Several approaches for the synthesis of TiO 2 have been reported, such as sol-gel, hydrothermal, solvothermal, and spray pyrolysis [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%